Perancangan Mesin Auto Stacking Kanal C dengan Kapasitas 900kg - Achmad Syahrul Rohman; Mohammad Miftachul Munir; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Lift aircraft are an important part of the fabrication industry so they become more efficient in terms of time and power. In a fabrication industry the manufacture of C canals the buildup process is still done manually with two people. So that there is a need for a lift aircraft to facilitate the preparation of C canals with dimensions of 45 cm x 49 cm x 600 cm or a total weight of 900 kg to be more efficient. The method used in the manufacture of this machine concept is ulrich method and then continued by analyzing the calculation of the engine and skeletal analysis. The analysis was conducted on this study using Fusion 360 software. The planning results were obtained by the conveyor engine using a 0.75 kW electric motor and using a 6.78 Nm stepper motor for rack gear shafts. The material used for the frame is the ASTM A36 and for the shaft is S45C. The result of the analysis on the upper frame is 44.93 MPa, for the lower frame is 48.09 MPa and for the towing profile is 39.26 MPa. The total cost for the manufacture of auto stacking machines is obtained from the calculation of rawmaterial costs and manufacturing costs. At the cost of raw materials making this machine amounted to Rp 99,062,000, while for manufacturing costs amounting to Rp 5,610,000. So that the total cost for manufacturing amounted to Rp 104,672,000.